Underwater environment laser ghost imaging based on Walsh speckle patterns - Yang, Mochou; Wu, Yi; Feng, Guoying (Frontiers in Physics, 2023)
Underwater imaging is a challenging task due to the effects of scattering and absorption in the water. Ghost imaging (GI) has attracted increasing attention because of its simple structure, long range, and achievable under weak light intensity. In underwater environment, conventional imaging is limited by low sensitivity, resulting in fuzzy images, while GI can solve this problem. In this study, underwater laser GI based on Walsh speckle patterns is proposed. According to the simulated and experimental results, noise resistance and low sampling rate of GI based on Walsh speckle patterns is proved. As the turbidity of the underwater environment increases, the imaging quality of GI based on Walsh speckle patterns decreases, but it is still much better than that of GI based on random speckle patterns and Hadamard speckle patterns while conventional imaging is no longer distinguishable. GI based on Walsh speckle patterns can be performed with the sampling rate lower than 10 %, the peak signal-to-noise ratio and the structural similarity of the result increases by 150.15 % and 396.66 %, respectively, compared with random speckle patterns GI. An identifiable image of GI based on Walsh speckle patterns can be reconstructed with a sampling rate of 6 % in a turbid water environment, which is simulated with the concentration of the milk powder not higher than 11.0 g/L. This method promotes the further development of optical imaging technology for underwater targets with a low sampling rate based on GI.